ANALISIS KUALITAS STANDARD STRENGTH PADA PORTLAND COMPOSITE CEMENT DENGAN METODE CONTROL CHART DAN EVALUASI KAPABILITAS PROSES PRODUKSI - Riza Sasmita; Yenni Kurniawati; Dina Fitria (Jurnal Gaussian, 2025)
The quality of cement products can be determined based on the results of standard strength tests, which are carried out using cube-shaped test samples through a compression testing machine. In the context of a continuously developing manufacturing industry, the demand for high-quality cement in Indonesia has also increased significantly. Therefore, it is necessary to implement production process control to ensure consistent quality that meets market needs.  The main focus of the research is on evaluating process stability and the process's ability to meet standard strength specifications using the X-bar and R control chart methods and process capability calculations. The results show that process variability is under statistical control when viewed from the R control chart, but the process average is not under statistical control, as indicated by 8 out of 21 points outside the control limits on the X-bar control chart. These points were identified as variations due to common causes inherent in the process. Nevertheless, process capability analysis showed that the process was technically capable of meeting specifications, with a Cp value of 4.35. Therefore, it was concluded that the Standard Strength production system at the company was capable despite statistical variation in the process mean.